Resolution is not the end: the Macklin effect after chest tube removal in a trauma patient with aging and comorbidities: a case report - Faye Abdulkareem; Fayez G. Aldarsouni; Sahar Alomar; Zisis Touloumis; Hussain M. AlHassan; Ghassan Z. Al Ramahi; Tareq Alsabahi; Khaled Twier; Mohammad Alsenani; Emad Alamoudi (Journal of Trauma and Injury)
Pneumomediastinum is an uncommon complication in cases of blunt chest trauma but can signal severe underlying issues. This report discusses a 69-year-old male patient with preexisting conditions of obesity, sleep apnea, and asthma, who experienced delayed pneumomediastinum and pneumopericardium following the removal of a chest tube. This tube had been placed to address a traumatic hemopneumothorax, which had resolved. The removal of the chest tube triggered a series of events, exacerbated by the patient's chronic health conditions. The patient was managed conservatively with close monitoring and physiotherapy, which successfully resolved the condition without the need for further invasive procedures. The multifactorial nature of the Macklin effect illustrates that even routine procedures such as chest tube removal can trigger a chain reaction in susceptible patients. The choice of conservative management, rather than immediate invasive interventions, underscores the delicate balance necessary in trauma care.